GO:eARth : a mobile application that encourages recycling (A) - Chan, Jin Xuan (Nanyang Technological University, 2020)
A circular economy is designed such that remove waste from the resource ecosystem while maximising the value of resources and extending the life expectancy of such resources as much as possible. For a circular economy to work, there is a precedence in trying to reduce, reuse and recycle our waste. These 3 principles have been inculcated from young to assimilate good habits for a sustainable future. By implementing the circular economy concept, Singapore is aiming to increase the rate of national recycling rate to 70%. Currently there are many kinds of materials that can be recycled, and it will continue to rise. Despite the high number of different kinds of materials that can be recycled, there are still confusion as to what can be recycled. Thus, a better way of identifying recyclables is needed to be able to encourage more people to build up recycling habits. Although there are many who understands the importance of recycling, they are still ignorant to the issue of climate change and its impact on Singapore’s survivability. Due to the negligence, it is hard to encourage more to recycle habitually. By doing this project, good recycling habits can be inculcated by making it an engaging activity and making recycling easy allowing users to identify items that can be recycled. This project will be trying to create a convolutional neural network to recognise recyclables and integrate it into the mobile application.